A Macroporous Hydrogel Dressing with Enhanced Antibacterial and Anti‐Inflammatory Capabilities for Accelerated Wound Healing. (6th April 2020) - Huang, Wen‐Can; Ying, Rui; Wang, Wei; Guo, Yuning; He, Yongjun; Mo, Xinya; Xue, Changhu; Mao, Xiangzhao
Abstract: Here, a novel macroporous hydrogel dressing is presented that can accelerate wound healing and guard against bacteria‐associated wound infection. Carboxymethyl agarose (CMA) is successfully prepared from agarose. The CMA molecular chains are cross‐linked by hydrogen bonding to form a supramolecular hydrogel, and the hydroxy groups in the CMA molecules complex with Ag + to promote hydrogel formation. This hydrogel composite exhibits pH‐responsiveness and temperature‐responsiveness and releases Ag +, an antibacterial agent, over a prolonged period of time. Moreover, this hydrogel exhibits outstanding cytocompatibility and hemocompatibility. In vitro and in vivo investigations demonstrate that the hydrogel has enhanced antibacterial and anti‐inflammatory capabilities and can significantly accelerate skin tissue regeneration and wound closure. Astonishingly, the hydrogel can cause the inflammation process to occur earlier and for a shorter amount of time than in a normal process. Given its excellent antibacterial, anti‐inflammatory, and physicochemical properties, the broad application of this hydrogel in bacteria‐associated wound management is anticipated. Abstract : A macroporous hydrogel dressing with antibacterial and anti‐inflammatory properties is developed for accelerated wound healing. The hydrogel matrix is formed by hydrogen bonding and supramolecular complexation. The hydrogel shows outstanding biocompatibility and can significantly accelerate skin tissue regeneration and wound closure.